Clinical outcomes of hypofractionated image-guided multifocal irradiation using volumetric-modulated arc therapy for brain metastases. (17th November 2018) - Furutani, Shunsuke; Ikushima, Hitoshi; Sasaki, Motoharu; Tonoiso, Chisato; Takahashi, Ayaka; Kubo, Akiko; Kawanaka, Takashi; Harada, Masafumi
Abstract: Volumetric-modulated arc therapy (VMAT) can be used to design hypofractionated radiotherapy treatment plans for multiple brain metastases. The purpose of this study was to evaluate treatment outcomes of hypofractionated image-guided multifocal irradiation using VMAT (HFIGMI–VMAT) for brain metastases. From July 2012 to December 2016, 67 consecutive patients with 601 brain metastases were treated with HFIGMI–VMAT at our institution. The prescribed dose was 50 Gy to a 95% volume of the planning target volume in 10 fractions. Fifty-five of the 67 patients had non-small-cell lung cancer, and the remaining 12 had other types of cancer. The median number of brain metastases was five, and the median maximum diameter was 1.2 cm. The median duration of follow-up was 12.0 months (range, 1.9–44.8 months), and the median survival time 18.7 months. Four patients with six lesions had local recurrences. The local control rate in the 64 assessed patients was 98.4% and 95.3% at 6 and 12 months, respectively (three died before assessment). The local control rate for the 572 assessed lesions was 99.8% and 99.3% at 6 and 12 months, respectively. Thirty-nine patients developed distant brain metastases, the distant brain control rate being 59.7% and 40.5% at 6 and 12 months, respectively. Acute toxicities were generally mild (Grade 1–2). Three patients (4.5%) developed radiation necrosis requiring corticosteroid therapy. The HFIGMI–VMAT technique with flat dose delivery was well tolerated and achieved excellent local control. This technique is a promising treatment option for patients with multiple and large brain metastases.